2012
DOI: 10.1111/j.1523-1739.2011.01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Habitat Quality, Population Size, Patch Size, and Connectivity on Patch‐Occupancy Dynamics of the Middle Spotted Woodpecker

Abstract: Despite extensive research on the effects of habitat fragmentation, the ecological mechanisms underlying colonization and extinction processes are poorly known, but knowledge of these mechanisms is essential to understanding the distribution and persistence of populations in fragmented habitats. We examined these mechanisms through multiseason occupancy models that elucidated patch-occupancy dynamics of Middle Spotted Woodpeckers (Dendrocopos medius) in northwestern Spain. The number of occupied patches was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 38 publications
9
93
1
1
Order By: Relevance
“…[5,22 -24]). Under severe fragmentation conditions, small local populations of woodpeckers are subjected to a high extinction risk associated with demographic and environmental stochasticity [5]. Previous research shows the existence of floaters that may replace the lost breeders in the Cantabrian Mountains [25,26], further indicating the suitability of our study system for testing floater-related hypotheses of population persistence and turnover.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[5,22 -24]). Under severe fragmentation conditions, small local populations of woodpeckers are subjected to a high extinction risk associated with demographic and environmental stochasticity [5]. Previous research shows the existence of floaters that may replace the lost breeders in the Cantabrian Mountains [25,26], further indicating the suitability of our study system for testing floater-related hypotheses of population persistence and turnover.…”
Section: Introductionmentioning
confidence: 81%
“…population size, patch size and the intrinsic habitat quality of local patches; e.g. [5]), local populations will have low extirpation propensity in patches where floaters occur.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that retention of dead trees in coniferous forests may substantially increase habitat quality, i.e. this may be a driver of patch-occupancy dynamics and species density (van Horne 1983;Johnson 2007;Robles and Ciudad 2012), which is generally unsuitable even for a generalist woodpecker species, because of the low number of native deciduous trees suitable for excavation (Barrientos 2010). It has been suggested that with increasing numbers, the great spotted woodpecker is able to exploit living trees as well as dead snags that are available (Smith 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We use the term ''territory'', because middle spotted woodpeckers defend almost exclusive territories during March and April, with both sexes participating to similar degrees in territorial defense (Pasinelli et al 2001). On the basis of our long-term experience, we assumed that two registrations in the pre-breeding period was sufficient to accept a territory (Lõhmus et al 2016;Stachura-Skierczyńska and Kosiński 2016), and to exclude transient/floater birds (Pasinelli et al 2001;Robles and Ciudad 2012). Moreover, two visits allow an experienced observer to find almost 100% of territories in the pre-breeding period (Z. Kosiński unpubl.…”
Section: Woodpecker Occurrence Datamentioning
confidence: 99%
“…That is, inferring processes driving local extinction from patterns of occurrence, such as snapshot presence/absence data, or focusing on population turnover (following a meta-population approach sensu Hanski and Gaggiotti 2004). Therefore, the majority of studies have focused on occupancy dynamics rather than on the demographic processes underlying spatial patterns of patch occupancy (Frey et al 2012, Robles andCiudad 2012). Hence, they have examined the ultimate effects rather than the proximate causes of population turnover (Fig.…”
Section: Introductionmentioning
confidence: 99%